2001
DOI: 10.1080/15287390151101547
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Organic Compounds in Smoke at Experimental Fires

Abstract: Significant associations between firefighting and cancer have been reported; however, studies finding toxic products of combustion at municipal fires have been limited by (1) technical difficulties encountered at the scene of working fires, (2) the lack of a coherent sampling strategy, and (3) the absence of verified sampling methods. The objective of the present study was to characterize the presence of volatile organic compound (VOC) combustion products in fire smoke. Air samples from experimental fires burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…The most extensively studied class of combustion products was inorganic gases. A small number of studies also investigated other pollutants including VOCs [27,31,32,35,39,44], PAHs [27][28][29]31,33,37,38,[45][46][47][48], dioxins and/or other persistent organic pollutants [33,40,47,[49][50][51][52] and particle size distribution [45,53]. Organic compounds were considered to be a potential hazard, but in most studies individual compounds have not been identified or quantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensively studied class of combustion products was inorganic gases. A small number of studies also investigated other pollutants including VOCs [27,31,32,35,39,44], PAHs [27][28][29]31,33,37,38,[45][46][47][48], dioxins and/or other persistent organic pollutants [33,40,47,[49][50][51][52] and particle size distribution [45,53]. Organic compounds were considered to be a potential hazard, but in most studies individual compounds have not been identified or quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally studies were conducted to assess emissions from a range of burning materials under well-controlled conditions during small bench-scale experiments [26][27][28][29][30][31][32][33][34][35][36][37][38], emissions from largescale simulated room fires which were set up with a variety of furnishing materials [39][40][41][42] and emissions from vehicle fires [43]. These studies provide essential information on air pollutants released during combustion of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides glutamine synthetase and glutamate synthase for ammonium assimilation, the three genomes contain a conserved operon coding for an ammonium transporter (AmtB) and a nitrogen regulatory protein (GlnB) (Supplementary Table S7). Air carries numerous volatile organic compounds, prominent among which is CO (Austin et al, 2001). Study of the genomes revealed that Bs, Mm and Go have several copies of the coxLMS operon (Supplementary Table S7), which would help them oxidize CO.…”
Section: First-line Defense Strategiesmentioning
confidence: 99%
“…Hand-to-mouth contamination, contamination inside masks, and dermal absorption also may be important factors affecting chemical absorption. Although some chemicals are common to most fires (Austin et al 2001), neither knowledge of the burning materials nor environmental measurements can accurately predict the absorbed dose of combustion products. Recent studies have focused on acutely toxic firefighter exposures and specific aspects of firefighter response (Hartzell 1996); however, there has not been a comprehensive biomonitoring assessment of firefighters after a major incident.…”
mentioning
confidence: 99%